The Influence of the work environment on Employee Performance of PT Bloods Inc - Fauzobihi, Fauzobihi; Permana, Fadillah Dian; Rahman, Erik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In the family of human resources science, environment and discipline and employee performance are a unit that certainly affects employee performance. This study uses quantitative research, and work discipline plays an important role in determining the level of performance. The performance of the employee in question can be seen from the work results achieved by the employees in terms of quality and quantity according to their duties and responsibilities. In this research, employee work disciplie suggests that performance is one of the elements used in employee assessment which includes discipline to their work, position and organization. This discipline is reflected by the employee's willingness to protect and defend the organization inside and outside of work from being undermined by irresponsible people